N-Acetyl-Glucosamidase as Biomarker for Acute Kidney Injury - Aulia Annisa Rizki; Zulkifli Zulkifli; Agustina Br Haloho; Zen Hafy (HM Publisher, 2018)
Background : The estimated inciÂdence of Acute Kidney Injury (AKI) is two to three cases per 1,000 patients. Seven percent of hospitalized patients and about two-thirds of patients in intensive care units develop acute kidney injury and the mortalÂity rates range between 25 and 80 percent. Disruption in epithelial brush border of proximal tubular cell causes N-Acetyl-Î²-D-Glucosaminidase (NAG) to be released to the urine and the amount of enzyme could be directly correlated with tubular disruption. Objective : The aims of this research is to determine the sensitivity and specificity of NAG urine examination as an early biomarker for acute kidney injury. Methods : Thereâ€™s 66 subjects who met the inclusion criteria. All the subject were checked for the NAG urine level with Cloud Clone kit and creatinine serum were also checked 48 hours after admission. Results : The results showed in the cut-off point of 7.98 Ng/mL, urine NAG has a sensitivity of 68.6% and specificity 77.4%, positive predictive value 77.42%, negative predictive value 68.57 % and accuracy of 72.73% Conclusions : The result shows that urine NAG examination is more sensitive and specific as an early biomarker for Acute Kidney Injury compared to creatinine serum. Key words : Acute Kidney Injury, N-Acetyl-Î²-D-Glucosaminidase , sensitivity, spesificity